Heroes on horseback a life and times of the last gaucho caudillos - Chasteen, John Charles 1955- (Albuquerque University of New Mexico Press, 1995)
"Well-written study of 19th-century caudillismo and border politics looks at both leaders and followers during the 1893-94 Federalist War and subsequent uprisings in Uruguay. The caudillos were charismatic leaders who embodied the values and aspirations of the rural masses on both sides of the border, values represented by the 'myth of the patriada.'"--Handbook of Latin American Studies, v.58.uhttp://www.loc.gov/hlas.
Includes bibliographical references (pages 217-232) and index.
Keywords: Saravia, Aparicio -- 1855-1904.; Saraiva, Gumersindo -- 1852-1894.; Caudillos -- Uruguay -- History; Caudillos -- Brazil -- Rio Grande do Sul -- History; Uruguay -- History -- 1875-1904.; Rio Grande do Sul (Brazil) -- History -- Federalist Revolution